Clinical Effects and Safety of Electroacupuncture for the Treatment of Poststroke Dysphagia: A Comprehensive Systematic Review and Meta-Analysis. (26th September 2020) - Huang, Jinke; Shi, Yao; Qin, Xiaohui; Shen, Min; Wu, Manli; Huang, Yong
Abstract : Objectives . Electroacupuncture (EA), an extension of acupuncture, which is based on traditional acupuncture combined with modern electrotherapy, is commonly used for poststroke dysphagia (PSD) in clinical treatment and research. However, there is still a lack of sufficient evidence to recommend the routine use of EA for PSD. The aim of this study was to assess the efficacy and safety of EA in the treatment of PSD. Methods . Randomized controlled trials (RCTs) evaluating the effects of EA on PSD were identified through a comprehensive literature search of the PubMed, Embase, Cochrane Library, Web of Science, Chinese National Knowledge Infrastructure, Chinese Biomedical Database, and VIP databases from their inception to July 2020. The quality assessment of the included trials was performed based on the guidance of the Cochrane Reviewers' Handbook, and meta-analysis (MA) was performed by using the RevMan 5.3 software. Results . Sixteen trials were identified, and these included 1, 216 patients with PSD. The results demonstrated that EA in combination with swallowing rehabilitation training (SRT) was significantly superior to SRT alone with regard to effective rate (OR 5.40, 95% CI [3.78, 7.72], P < 0.00001, water swallow test (WST) (MD −0.78, 95% CI [−1.07, −0.50], P < 0.00001 ), the video fluoroscopic swallowing study (VFSS) (MD 1.47, 95% CI [1.11, 1.84], P < 0.00001 ), the Ichiro Fujishima Rating Scale (IFRS) (MD 1.94, 95% CI [1.67, 2.22], P < 0.00001 ), and the incidence of aspiration pneumonia (IAP) (OR 0.20, 95% CI [0.06, 0.61], P = 0.005 ). Conclusions . The results showed that EA was better than the control treatment in terms of the effective rate, WST, VFSS, IFRS, and IAP of dysphagia after stroke. Strict evaluation standards and high-quality RCT designs are necessary for further exploration.